Self-Regulated Learners: A Comprehensive, Translational Framework for Students with Learning Disabilities. Issue 1 (1st January 2023) - Johnson, Evelyn; Masser, Julianne S.; Spears, Lindsey
ABSTRACT: Recent advances in the science of learning and development suggest that education reform efforts will require approaches that attend to the needs of the whole student, to include intensive interventions for students who face barriers to learning, such as students with learning and attention disorders. Although the science of learning and development has been informed by research from multiple disciplines, special education teachers will be the primary drivers of this work. As such, they need a framework and tools to guide intervention that relies on the use of individualized, integrated, evidence-based strategies that support the varied self-regulatory challenges of students with learning and attention disorders. To address this need, we drew from both clinical practice and research, to develop a translational framework of self-regulated learning. We discuss how the five competencies of the framework can be used to design and deliver intervention to students with learning disabilities.